THE STUDY OF OPTICAL PROPERTIES OF MgxN1-xFe2O4/SiO2 NANOCOMPOSITE AGAINST THE METHYLENE BLUE PHOTODEGRADATION - Putra, Rachmad Almi; Fajriani, Fajriani; Alamsyah, Wan; Wahyuningsih, Puji; Sahputra, Hendri (Jurnal Neutrino, 2019)
The synthesis of MgxN1-xFe2O4/SiO2 composite nanoparticles, where x=0; 0.25; 0.5; 0.75; 1.0 through coprecipitation method and low temperatures had been successfully carried out. The result of X-ray Diffractometer (XRD) informed that the sample had crystalline forms and different crystallite sizes as the Mg concentration in the sample is increased. The sizes of crystallite produced were between 12.12 to 24.47 nm. In addition, theoretically and experimentally there were differences grid parameters with the energy bandgap of the nanocomposite sample ranged from 2.51 to 2.66 electron volt (eV). Therefore, the MgxN1-xFe2O4/SiO2composite nanoparticles could be referred to the nano-photocatalyst or nano-adsorbent for organic pollutant due to its potential to degrade Methylene Blue waste.